Regulatory Role of Ubiquitin in Eukaryotic DNA Translesion Synthesis - Yang, Kun; Weinacht, Christopher P; Zhuang, Zhihao (Biochemistry (Easton), 2013)
Although often associated with proteasome-mediated protein degradation, ubiquitin plays essential nondegradative roles in a myriad of cellular processes, including chromatin dynamics, membrane trafficking, innate immunity, and DNA damage response. The recent progress in understanding DNA translesion synthesis (TLS), an important branch of DNA damage response, has largely been stimulated by the finding that ubiquitination of an essential nuclear protein, proliferating cell nuclear antigen (PCNA), controls precisely how eukaryotic cells respond to DNA damage. Despite the remarkable activity of the TLS polymerases in synthesizing past the damaged nucleotides, they are intrinsically error-prone on the normal DNA template. Therefore, a stringent regulation of the TLS polymerases is essential for the faithful replication of the DNA genome. Here we review the structure and function of the Y-family TLS polymerases and their interactions with ubiquitin and monoubiquitinated PCNA (Ub-PCNA). Driven by the need for monoubiquitinated PCNA in a sufficient quantity and purity, researchers developed both chemical and enzymatic methods for PCNA monoubiquitination, which have propelled our understanding of the structure of Ub-PCNA by X-ray crystallography and small-angle X-ray scattering. Together with studies using a reconstituted polymerase switching assay, these investigations revealed a surprising conformational flexibility of ubiquitin as a modifier on PCNA. Although the molecular details of TLS in cells still need to be deciphered, two working models, polymerase switching and postreplicative gap filling, have been proposed and tested in both in vitro and cellular systems. Evidence for both models is discussed herein. Compared to PCNA monoubiquitination, polyubiquitination of PCNA in DNA damage response is much less well understood and will be the subject of a future investigation. Given the close connection of DNA damage response and anticancer therapy, an in-depth understanding of the eukaryotic translesion synthesis and its regulation by ubiquitin will likely provide new opportunities for therapeutic intervention.